The Impact of Ethic and Competence on Audit Quality: Accountability as Moderating Variable - Robby Saputra; Amrie Firmansyah (Studi Ilmu Manajemen dan Organisasi, 2024)
Purpose: This study used accountability as a moderating variable to examine the impact of ethics and competence on audit quality. Methodology: The data used in this study were derived from a questionnaire survey distributed to respondents from October to December 2023. The respondents for this study were Badan Pemeriksa Keuangan (BPK) head office auditors at State Financial Auditor III. The respondents were selected using purposive sampling criteria. The final sample comprised 69 respondents. This study used the structural equation Modelling (SEM) approach with Smart Partial Least Square (PLS) software to analyze the data.Results: The findings show that ethics and competence positively affect audit quality. Accountability as a moderating variable strengthens the impact of ethics on audit quality. However, accountability does not influence the effect of competence on audit quality.Conclusions: This research concludes that the ethics and competence of BPK’s auditors positively affect the quality of audit reports. In other words, better compliance with the code of ethics and continuous improvement of competence will improve the quality of audit reports.Limitations: This research used a method of distributing questionnaires to several respondents online so that the questions from respondents regarding the questionnaires could not be confirmed directly. In addition, this study uses only two audit attributes as determinants of audit quality.Contribution: This research will provide an understanding of BPK stakeholders regarding the importance of ethics and competence for BPK auditors. Additionally, it is expected that they will not attempt to influence BPK auditors to commit ethical violations. Furthermore, this research is meritorious for BPK to investigate the factors that can encourage the accountability of auditors’ attitudes to improve audit quality.